Reflect on fundamental, modeling and control of industrial robotic manipulators for simulation purposes - Chen, Chin Jin; Rahman, Ramhuzaini Abd; Wahab, Hanani Abd; Yee, Low Cheng (AIP conference proceedings, 2023)
Robotic manipulators have long been used in industries due to its capability to perform various tasks that require high precision and repetitive in nature. Besides, robotic manipulations are also ideal for applications in the environment that is not conducive to human. With the emerging of Industry 4.0, robotic manipulators are expected to play more important role in the manufacturing sector as higher productivity is required. For that, many robotic related courses have been offered at the undergraduate level to equip students with knowledge of this technology. To understand the technology, demonstration using an actual robotic manipulator setup is necessary. Nevertheless, acquiring setup of the manipulator is quite expensive and if purchase, the quantity and access to the manipulator will be limited. As a result, sufficient amount of time will not be provided for students to explore and learn how the robotic manipulator is actually working. Alternatively, simulator can be used as a learning tool to understand the robotic manipulator. Besides cost-effective, students have unlimited access at their own convenient time. Utilizing the Project Based Learning (PjBL) approach, this paper is written to provide essential information for the final year undergraduate mechanical engineering students of Universiti Tun Hussein Onn Malaysia to build their own path control robotic simulator. At the end of semester, students will be presenting their simulator in group for evaluation purpose. The best simulator will be selected as a learning tool and subject to further improvise in the upcoming semester.